Extraction of Microcrystalline Cellulose and Silica from Agriculture Waste and Its Application in Synthesis of Wheat Gluten and Fish Scales Derived Bioplastic - S. Samraj; K. Senthilkumar; P. Induja; M. Venkata Ratnam; G. V. Aatral; G. V. S. Ramakrishna (International Journal of Biomaterials)
Plastics play a significant part in human life and the world we live in. The use of plastics results in detrimental effects on the natural world, which compels us to look for viable replacements. As a result of their enhanced capacity to biodegrade, bioplastics are becoming increasingly important materials. In recent years, there has been a rapid ascent in the utilization of biopolymers in various applications. The objective of this research is to investigate the impact that silica obtained from rice hull ash (RHA) and microcrystalline cellulose (MCC) obtained from groundnut husk have on the properties of bioplastic obtained from wheat gluten and fish scales. The usage of fish scales has been shown to have a positive effect on weight reduction and debasement rates. Microcrystalline cellulose (MCC) is utilized in a wide range of concentrations, and the influence of MCC on bioplastic is researched. The biodegradability tests of bioplastic revealed that the plastic lost 35% of its weight in just 14 days. The experiments that were done to evaluate the chemical stability and tensile strength of the bioplastic indicated that the MCC content has a significant effect in improving the characteristics of the material.